Bioremediation of batik wastewater by Rhizobacteria isolated from iron sand soils tolerant of Pb and Zn: Rhizobacteria tolerant of Pb and Cd (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Oedjijono, Lestari S, Samsudin LS, Hermilia. 2021. Bioremediation of batik wastewater by Rhizobacteria isolated from iron sand soils tolerant of Pb and Zn. Biodiversitas 23: 299-305. Rhizobacteria originated from Iron sand soils are thought to be resistant to heavy metals because they are adapted to metal-contaminated environments. Batik industry produces pollutants containing organic substances, solid suspension, and heavy metals such as Lead (Pb) and Zinc (Zn). The objectives of this study were to select and determine the identity of Rhizobacterial isolates tolerant of Pb and Zn metals, to investigate their ability and the optimum pH in tolerating and reducing the concentrations of Pb and Zn in batik wastewater. The results found five Rhizobacterial isolates of Rb2, Rb6, Rb7, Rb8, and Rb12 showing high tolerance to Pb and Zn metals. The adsorption capacity of selected Rhizobacterial isolates of Rb2, Rb8, and Rb12 on Pb was significant at pH 5.5-6.0 with the mean concentration of Pb reduced was 2.836 mg/L (80%), while against Zn by isolates of Rb6, rb7, and Rb12 was high at pH 5.5 with a reduced concentration of 0.8761 mg/L (43.2%). The selected Rhizobacterial isolates of Rb2 and Rb6 were identified as members of the genus Pseudomonas, Rb7 and Rb8 belonged to the genus Lactobacillus, while Rb12 was a species member of the genus Staphylococcus.
Keywords: Keywords: Adsorption capacity, iron sand soils, Pb and Zn bioremediation, Rhizobacteria